Regional cooperation in hydrology in the Nordic countries: an information note (1972)
Working paper on regional cooperation in hydrology between Denmark, Finland, Iceland, Norway and Sweden, within the framework of the International Hydrological Decade - Covers exchange of publications and dissemination of information, reports on the establishment of hydrological networks and on steps taken towards standardization, refers to meetings and seminars